The Effect of Apis mellifera L. Pollination on Seed Yield and Nutritional Qualities of Sesamum indicum L. in Dale Sedi District of Western Oromia, Ethiopia - Ofijan Tesfaye; Elias Gaisa (Legume Science, 2024)
ABSTRACT The development of blossoming seed plants that provide a genetically diverse crop of progeny depends on pollination. Sesamum indicum is an oilseed crop and requires both self and cross‐pollination that varies based on insect type, crop variety, and environmental factors. Hence, the experiment was conducted for two consecutive years (2022 and 2023) to the effect of Apis mellifera L. pollination on yield, germination, and nutritional qualities of S. indicum (Dicho variety). A completely randomized block design with three treatments was used, and each treatment was replicated four times. Insects from open plot were counted from 1 m × 1 m quadrant/5 min. Seed yield and yield parameters and germination rates were recorded based on standard methods. Oil content was analyzed by Soxhlet extraction. From the study, 13 insects were identified of which 69.2% were categorized under the order Hymenoptera. A combined mean of plant height, branch/plant, and number of pod/plant showed statistically no difference (p > 0.05) among treatments. However, the number of seeds/pod, 1000 seed weight, and yield (quintal)/ha produced by an open plot and a plot caged with A. mellifera were statistically higher (p < 0.05) as compared with the closed plot. The percentage increment in seed yield (quintal)/ha were 17.16% and 20.33% for the open plot and the plot caged with bees, respectively. The seed germination was found to be maximum in the open plot (88.9%) followed by a plot caged with A. mellifera (86.68%) and a closed plot (60.46%). A measurable variation (p < 0.05) in oil content(%) was recorded among the treatments with the maximum from a plot caged with bees (54.24 ± 0.27) followed by an open plot (52.04 ± 0.58) and closed plot (48.81 ± 0.24). These findings suggest that pollinators, including honey bees, A. mellifera visiting S. indicum can enhance yields, germination rates, and oil content.